2006
DOI: 10.1096/fj.06-5898fje
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 2 and basement membrane integrity: a unifying mechanism for progressive renal injury

Abstract: Chronic kidney disease (CKD) and failure are problems of increasing importance. Regardless of the primary etiology, CKD is characterized by tubular atrophy, interstitial fibrosis, and glomerulosclerosis. It has been assumed that diminished matrix metalloproteinase (MMP) activity is responsible for the accumulation of the extracellular matrix (ECM) proteins and collagens that typify the fibrotic kidney. Here we demonstrate that transgenic renal proximal tubular epithelial expression of a specific enzyme, MMP-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
185
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(199 citation statements)
references
References 44 publications
6
185
1
6
Order By: Relevance
“…29,30 MMP-2 appears both necessary and sufficient to induce tubular EMT. 19,21 Similarly, a recent study using transgenic mice with targeted expression of active MMP-2 in the proximal tubular epithelial cells has demonstrated Figure 6 The expression of mesenchymal marker proteins, including S100A4 (a, f, k), vimentin (b, g, l), and a-smooth muscle actin (aSMA) (c, h, m), marker of collagen synthesis heat shock protein-47 (HSP-47), which is known as the collagen-specific molecular chaperone (d, i, n), and macrophage infiltration (F4/ 80) (e, j, o), at day 14 post-unilateral ureteral obstruction (UUO) in MMP-2 þ / þ mice (a-e: WT mice), MMP-2 À/À mice (f-j: MMP-2 KO mice), and MMP-2 þ / þ mice treated with minocycline (k-o: Minocycline) (a-o, Â 400). In MMP-2 þ / þ mice at day 14 post-UUO, the expression of S100A4, vimentin, aSMA, and HSP-47 was evident in damaged tubular epithelial cells and interstitial cells (arrowhead in panels a-d).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 MMP-2 appears both necessary and sufficient to induce tubular EMT. 19,21 Similarly, a recent study using transgenic mice with targeted expression of active MMP-2 in the proximal tubular epithelial cells has demonstrated Figure 6 The expression of mesenchymal marker proteins, including S100A4 (a, f, k), vimentin (b, g, l), and a-smooth muscle actin (aSMA) (c, h, m), marker of collagen synthesis heat shock protein-47 (HSP-47), which is known as the collagen-specific molecular chaperone (d, i, n), and macrophage infiltration (F4/ 80) (e, j, o), at day 14 post-unilateral ureteral obstruction (UUO) in MMP-2 þ / þ mice (a-e: WT mice), MMP-2 À/À mice (f-j: MMP-2 KO mice), and MMP-2 þ / þ mice treated with minocycline (k-o: Minocycline) (a-o, Â 400). In MMP-2 þ / þ mice at day 14 post-UUO, the expression of S100A4, vimentin, aSMA, and HSP-47 was evident in damaged tubular epithelial cells and interstitial cells (arrowhead in panels a-d).…”
Section: Discussionmentioning
confidence: 99%
“…21 Therefore, in addition to the pathogenic role of MMP-2 activity in the migration of tubular epithelial cells with mesenchymal phenotype into the interstitium accompanied by the destruction of TBM, recent studies have also indicated that MMP-2 can trigger EMT, probably through the disruption of TBM integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-2 with relative molecule weight 72,000, a kind of collagenase A, may degrade collagen IV [3]. The disorder of MMP-2 expression might induce changes in tubular basement membrane structure, thus resulting to renal tubular epithelial cell transdifferentiation with tubular atrophy, fibrosis and renal dysfunction [4]. MMP-2 participates in the degradation of ECM, however TIMP-1 regulates its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mice doubly deficient in these enzymes still achieve normal embryonic BM transmigration events such as pancreatic islet cell formation, suggesting that MMP-2 and MMP-9 are not essential for cellular invasion and migration [23,59]. The roles of MMP-2 and MMP-9, as well as the other MMPs, within the cancer microenvironment are still being fully characterized [23,[60][61][62].…”
Section: Remodeling Of the Bm And Ecm In Cancermentioning
confidence: 99%